Kinerja karyawan di sektor perbankan: Peran kepuasan kerja, komitmen organisasi, dan keadilan prosedural pada Bank Majalengka - Asep Qustolani; Siti Awah Wulandari (Journal of Management and Digital Business, 2026)
Employees constitute a key strategic asset for organizations, as they play a central role in ensuring sustainability and achieving organizational goals. However, prior studies have reported inconsistent findings regarding the effects of job satisfaction, organizational commitment, and procedural justice on employee performance, particularly within the context of regional banking, which remains underexplored. This condition indicates a research gap that warrants further empirical investigation across different organizational settings. This study aims to examine the influence of job satisfaction, organizational commitment, and procedural justice on employee performance at Bank Majalengka. A quantitative approach was employed using a descriptive and verificative survey method, involving all 124 employees as respondents through a saturated sampling technique. Data were analyzed using multiple linear regression to assess the relationships among variables. The results reveal that job satisfaction, organizational commitment, and procedural justice have a positive and significant effect on employee performance, both partially and simultaneously. These findings suggest that strengthening psychological factors and ensuring fairness in organizational processes are essential strategies for fostering sustainable, adaptive employee performance.